2005
DOI: 10.1007/s11068-005-8360-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of connexins (Cx36, Cx43, Cx45), glutamate receptors and aquaporin-4 in rodent olfactory mucosa, olfactory nerve and olfactory bulb

Abstract: Odorant/receptor binding and initial olfactory information processing occurs in olfactory receptor neurons (ORNs) within the olfactory epithelium. Subsequent information coding involves highfrequency spike synchronization of paired mitral/tufted cell dendrites within olfactory bulb (OB) glomeruli via positive feedback between glutamate receptors and closely-associated gap junctions. With mRNA for connexins Cx36, Cx43 and Cx45 detected within ORN somata and Cx36 and Cx43 proteins reported in ORN somata and axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 96 publications
7
88
0
1
Order By: Relevance
“…Early on, it was proposed that neurons share gap junctions only with neurons, and that glia share intercellular gap junctions only with glia (Brightman and Reese, 1969;Mugnaini, 1986). This "restricted coupling partner" hypothesis gained support based on TEM and FRIL immunocytochemical data showing that neuronal, astrocytic and oligodendrocytic gap junctions each express different complements of connexins Nagy and Dermietzel, 2000;Rash et al, 2000Rash et al, , 2001bKamasawa et al, 2005;Fukuda et al, 2006), with Cx43, Cx30 and (in limited areas) Cx26 in astrocytes and leptomeninges (Li et al, 1997;Nagy et al, 1999Nagy et al, ,2001Rash et al, 2001b); Cx29, Cx32 and Cx47 in oligodendrocytes (Rash et al, 2001a(Rash et al, ,2001bNagy et al, 2004;Kamasawa et al, 2005); and Cx36 exclusively in neurons (Rash et al, 2001b;Fukuda et al, 2006), extending data from immunofluorescence analysis and thin-section immunocytochemistry (Yamamoto et al, 1990a(Yamamoto et al, ,1990bScherer et al, 1995;Mercier and Hatton, 2001;Altevogt et al, 2002;Kleopas et al, 2004;Rash et al, 2005).…”
Section: Connexin Composition Of Neuronal Vs Glial Gap Junctions In Lcmentioning
confidence: 99%
See 1 more Smart Citation
“…Early on, it was proposed that neurons share gap junctions only with neurons, and that glia share intercellular gap junctions only with glia (Brightman and Reese, 1969;Mugnaini, 1986). This "restricted coupling partner" hypothesis gained support based on TEM and FRIL immunocytochemical data showing that neuronal, astrocytic and oligodendrocytic gap junctions each express different complements of connexins Nagy and Dermietzel, 2000;Rash et al, 2000Rash et al, , 2001bKamasawa et al, 2005;Fukuda et al, 2006), with Cx43, Cx30 and (in limited areas) Cx26 in astrocytes and leptomeninges (Li et al, 1997;Nagy et al, 1999Nagy et al, ,2001Rash et al, 2001b); Cx29, Cx32 and Cx47 in oligodendrocytes (Rash et al, 2001a(Rash et al, ,2001bNagy et al, 2004;Kamasawa et al, 2005); and Cx36 exclusively in neurons (Rash et al, 2001b;Fukuda et al, 2006), extending data from immunofluorescence analysis and thin-section immunocytochemistry (Yamamoto et al, 1990a(Yamamoto et al, ,1990bScherer et al, 1995;Mercier and Hatton, 2001;Altevogt et al, 2002;Kleopas et al, 2004;Rash et al, 2005).…”
Section: Connexin Composition Of Neuronal Vs Glial Gap Junctions In Lcmentioning
confidence: 99%
“…In recent years, sensitive electrophysiological techniques have also documented electrical synapses in numerous adult brain regions (Bennett and Zukin, 2004); mRNA for the gap junction protein connexin36 (Cx36) was widely detected in neurons but not glia (Condorelli et al, 1998;Condorelli et al, 2000); and Cx36 was found to be present in ultrastructurally-defined gap junctions between neurons in many regions of both developing and adult CNS (Rash et al, 2001b;Nagy et al, 2004;Li et al, 2004a;Rash et al, 2005;Kamasawa et al, 2006;Fukuda et al, 2006). Moreover, the functional importance of Cx36 in adult brain is indicated by deficits in neuronal network properties and by behavioral impairments in Cx36 knockout mice (Hormuzdi et al, 2004;Frisch et al, 2005).…”
mentioning
confidence: 99%
“…A particular advantage of FRIL is that labeling specificity is assessed directly, based on restriction of immunogold labels to a single type of molecular array (e.g., gap junctions, tight junctions, postsynaptic densities, and AQP4 "square arrays") in ultrastructurally-identified cells, and consistent absence of that label from any other specific ultrastructural feature (Fujimoto, 1995(Fujimoto, , 1997 Rash et al, 2004b). In typical samples with low background, the "signal-to-noise ratios" ranged from 1000:1 to 15,000:1 [for details, see (Meier et al, 2004;Rash et al, 2005)]. …”
Section: Replica Cleaning In Sds and Immunogold Labelingmentioning
confidence: 99%
“…Goat anti-rabbit IgG conjugated to 10-nm and 20-nm gold beads was from Chemicon (Temecula, CA; no longer available), goat anti-rabbit IgG and goat anti-mouse IgG conjugated to the 6-nm, 12-nm, and 18-nm gold beads were from Jackson ImmunoResearch, and goat antirabbit IgG conjugated to 20-nm and 30-nm gold was from BBInternational, Ltd. (Ted Pella, Inc.). Controls included omission of primary antibodies to a target connexin, as well as doublelabeling some replicas for one connexin plus one non-connexin membrane protein [e.g., NMDA receptors (Rash and Yasumura, 1999;Rash et al, 2001bRash et al, , 2005 or aquaporin4 (AQP4) (Rash et al, 1998b;Furman et al, 2003)]. Labeled replicas were rinsed in distilled water, air dried at 60°C, and a stabilizing 20-nm coat of carbon was applied to the labeled side of the replica.…”
Section: Replica Cleaning In Sds and Immunogold Labelingmentioning
confidence: 99%
“…Four candidate gap junction-forming proteins [connexin36 (Cx36), connexin45 (Cx45), connexin50 (Cx50), and connexin57 (Cx57)] and two additional poreforming proteins [pannexin1 (Px1) and pannexin2 (Px2)] have been identified in central nervous system neurons (16)(17)(18)(19)(20)(21). To date, Cx36 is the only gap junction-forming protein documented in cortical GABAergic neurons, as established by ultrastructural methods (22).…”
mentioning
confidence: 99%